Keefektifan Penerapan Kurikulum Sekolah Minggu Oleh Pengajar Sekolah Minggu Di Jemaat GKI Elim Malanu Klasis Sorong: The Effectiveness of the Implementation of the Sunday School Curriculum by Sunday School Teachers at the GKI Elim Malanu Klasis Sorong Congregation - Mofu, Benyamin (MURAI: Jurnal Papua Teologi Konstekstual, 2024)
The effectiveness of the Sunday school curriculum implementation carried out by GKI Elim Malanu Sunday School Teachers has not been able to answer the needs of children. Sunday School teachers only bring material from the context of the Bible without making efforts to contextualize the Word into real situations experienced by children, such as cyberbullying and violence. This is due to the limited time and knowledge of Sunday school teachers in implementing Sunday school lessons. The research method used by researchers in this study is the descriptive-qualitative research method. According to Creswell J. W. (2017), qualitative research is a study whose main focus is researching social and human problems. The data source is obtained from observing and analyzing objects while in the field, then described in a report using words and not numbers in detail. The effectiveness of the implementation of the implementation of the Sunday school curriculum for Sunday school teachers can be determined by following several important points, including: basic courses for Sunday school teachers; self-study at home; continuous lesson preparation; and getting support from the church and parents. The effectiveness of Sunday school curriculum implementation by Sunday school teachers as an effort to improve the quality of Sunday school learning for children in the GKI Elim Malanu congregation, namely Sunday school teachers understand the central role of Sunday school teachers, improve qualifications and training for Sunday school teachers, support from parents and the church for Sunday school teachers, evaluation and continuous lesson preparation time, and collaboration.